Research Collaboration between Stockholm University and other Swedish Academic Institutions: A Bibliometric Study to Support Decisions on Library Collaboration - Ahlgren, Per; Hinders, Johan; Lindelöw, Camilla; Parmhed, Sara; Swedberg, Per (Qualitative and Quantitative Methods in Libraries, 2017)
Academic libraries collaborate in several ways. For instance, collaboration can concern standards for indexing and statistics, technical solutions or collection development. A question that a given academic library might ask is with which other academic libraries the library should principally collaborate. In this study, we show how bibliometric methods can be used to generate information that can support decision making with regard to the question at stake. We evaluate the amount of research collaboration between Stockholm University and other Swedish academic institutions across five publishing years, and for the whole considered time period, where research collaboration is operationalized as co-publishing. A dataset of publications obtained from Web of Science, where each publication has at least one Stockholm University address, is used in the study. Co-publishing rates, non-fractionalized and fractionalized, across the publishing years and for the whole for period, for Stockholm University and other Swedish academic institutions, are reported. Further, parts of the outcome of the study are visualized in terms of co-publishing networks.